PRODUKSI BIOMASS DAN HASIL TANAMAN JAGUNG DENGAN PENERAPAN MODIFIKASI PERTANAMAN UNTUK PRODUKSI PANGAN DAN PAKAN DI NTB - Eka Widiastuti; B. Tri Ratna Erawati (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2019)
Assessment of Maize Cultivation for Biomass and Seeds production in West Nusa Tenggara. Maize plants are quite potential to support the development of livestock in the province of West Nusa Tenggara. The purpose of this assessment was to identify the seeds and biomass production of 4 varieties of maize cultivated in West Nusa Tenggara (NTB). The research was conducted on dry season (first dry season or second planting season) from April to July 2012. Planting procedure consisted of population setting and timing of pruning for biomass production. The research was designed following Nested Design with 4 varieties of maize which were 2 varieties of hybrid Bima 3 and Bisi 16, and 2 varieties of composite Srikandi Kuning and Lamuru. The assesment was carried out in two locations, the first location was Semangat Patuh Farmer Group in Dusun Bila Kembar of Suela Village of Suela Sub-district of East Lombok Regency and the second one was in Pendi Janggi Farmer Group in Dusun Sekokok of Jorok Village of Utan Sub-district of Sumbawa Regency. The cultivation of each variety was repeated by 5 farmers comprised of 20 research plots in each location. The results of the assessment indicated that Bima 3 varieties produced the most biomass in Suela (8.06 tons/ha) at 95 days after planting while Srikandi Kuning (6.75 tons/ha) at 40 days after planting produced the most biomass in Utan. Bima 3 varieties seed production in Suela is 5.34 tons/ha and in Utan is 7.7 tons/ha.Keywords: maize, biomass, seeds, feed, West Nusa TenggaraABSTRAK Tujuan pengkajian ini adalah untuk mengetahui potensi produksi biji dan biomass 4 (empat) varietas jagung yang ditanam untuk pangan dan pakan di Nusa Tenggara Barat (NTB). Pengkajian dilakukan pada musim kemarau I (MK I) atau musim tanam II (MT II) pada bulan April hingga Juli 2012. Rancangan penelitian yang digunakan adalah rancangan tersarang dengan 4 (empat) varietas jagung yaitu 2 varietas hibrida yaitu Bima 3 dan Bisi 16, dan 2 varietas komposit yaitu Srikandi Kuning dan Lamuru. Pengkajian dilakukan di dua lokasi yaitu di kelompok tani Semangat Patuh di Dusun Bila Kembar, Desa Suela Kecamatan Suela, Kabupaten Lombok Timur (lokasi pengkajian 1) dan di kelompok tani Pendi Janggi di Dusun Sekokok Desa Jorok kecamatan Utan Kabupaten Sumbawa (lokasi pengkajian 2). Pengkajian untuk setiap varietas diulang 5 kali dengan menggunakan lahan petani sebagai ulangan sehingga diperoleh 20 petak lahan penelitian (masing-masing seluas 0,05 ha) di masing-masing lokasi. Hasil pengkajian menunjukkan bahwa varietas Bima 3 menghasilkan biomass terbanyak di Suela (8,06 ton/ha) pada 95 HST sedangkan Srikandi Kuning (6,75 ton/ha) pada 40 hari setelah tanam (HST) menghasilkan biomass terbanyak di Utan. Produksi biji varietas Bima 3 di Kecamatan Suela sebesar 5,34 ton/ha dan di Kecamatan Utan sebesar 7,7 ton/ha.Kata kunci: jagung, biomassa, biji, pakan, Nusa Tenggara Barat